Taxonomic Study of Lichens of Phulchowki Hills, Lalitpur District (Kathmandu Valley) - Devkota, A (Scientific World, 2010)
The lichens were collected from different altitudinal gradient ranges from 1500-2700 m. above sea level of Phulchowki hill. They were identified on the basis of their morphological, anatomical and chemical studies (colour reaction, thin layer chromatography and microcrystallography). A total of thirty-two species of lichens were identified which comprises nine families and ten genera. Among them family Parmeliaceae was largest one which comprises ten species. Key words: Lichens; Crustose; Foliose; Fructicose. DOI: 10.3126/sw.v6i6.2633 Scientific World, Vol. 6, No. 6, July 2008 44-51